KARAKTERISASI MORFOLOGI DAN OPTIMASI PRIMER INTER SIMPLE SEQUENCE REPEATS (ISSR) UNTUK STUDI AWAL KERAGAMAN GENETIK Syzygium zeylanicum (L.) - Faza, Ahmad Muwaffiq; Martiansyah, Irfan; Turhadi, Turhadi (Universitas Jambi, 2026)
Syzygium zeylanicum (Myrtaceae) is a species that grows in the Indo-Malayan region. Different growing environments for S. zeylanicum can influence morphological characteristics and reflect genetic diversity. The objective of this study was to describe the morphological characteristics of S. zeylanicum and optimize Inter Simple Sequence Repeats (ISSR) primers as an initial step toward studying the genetic diversity of S. zeylanicum. This study was conducted by collecting S. zeylanicum samples from the Bogor Botanical Garden at six locations: V.B.84, V.B.84a, II.Q.87, II.Q.87a, V.C.54a, and V.C.97a. Leaf and branch samples were collected for morphological characterization. DNA isolation was performed using 2% CTAB. Optimization was performed for 12 ISSR primers (ISSR1, ISSR2, ISSR3, ISSR4, ISSR5, ISSR6, ISSR7, ISSR8, ISSR9, ISSR10, ISSR11, and ISSR12) with annealing temperature ranges of 52 – 54 °C, 52.1 – 5 3.1 °C, 55 – 58 °C, and 45 – 50 °C. Characterization showed that S. zeylanicum leaves are simple, lanceolate, caudate tips, aequilateral bases, entire margins, brochidodromous venation, opposite leaf arrangement, petiolate attachment, abaxially glabrous, and adaxially lustrous. The leaf length, leaf width, and branch diameter of S. zeylanicum ranged from 6 – 8.7 cm, 2.3 – 3.03 cm, and 1.45 – 1.96 cm, respectively. In addition, 11 of the 12 ISSR primers successfully obtained optimal annealing temperatures, including ISSR1 (57.7 °C), ISSR2 (52.8 °C), ISSR3 (56.6 °C), ISSR5 (52.7 °C), ISSR6 (52.9 °C), ISSR7 (47.8 °C), ISSR8 (47.8 °C), ISSR9 (52.6 °C), ISSR10 (53.0 °C), ISSR11 (49.7 °C), and ISSR12 (49.0 °C). Only ISSR4 primer did not produce DNA bands after optimization at all temperature ranges used.